Neuronal correlates of attention and its disengagement in the superior colliculus of rat - Ngan, Nguyen H.; Matsumoto, Jumpei; Takamura, Yusaku; Tran, Anh H.; Ono, Taketoshi; Nishijo, Hisao (Frontiers in Integrative Neuroscience, 2015)
Orienting attention to a new target requires prior disengagement of attention from the current focus. Previous studies indicate that the superior colliculus (SC) plays an important role in attention. However, recordings of responses of SC neurons during attentional disengagement have not yet been reported. Here, we analyzed rat SC neuronal activity during performance of an attention-shift task with and without disengagement. In this task, conditioned stimuli (CSs) (right and/or left light-flash or sound) were sequentially presented. To obtain an intracranial self-stimulation reward, rats were required to lick a spout when an infrequent conditioned stimulus appeared (reward trials). In the disengagement reward trials, configural stimuli consisting of an infrequent stimulus and frequent stimulus in the former trials were presented; in the non-disengagement reward trials, only an infrequent stimulus was presented. Of the 186 SC neurons responding to the CSs, 41 showed stronger responses to the CSs in the disengagement reward trials than in the non-disengagement reward trials (disengagement-related neurons). Furthermore, lick latencies in the disengagement reward trials were negatively correlated with response magnitudes to the CSs in half of the disengagement-related neurons. These disengagement-related neurons were located mainly in the deep layers of the SC. Another 70 SC neurons responded to the CSs in both disengagement and non-disengagement reward trials, suggesting that these neurons were involved in attention engagement. Our results suggest complementary mechanisms of attentional shift based on two subpopulations of neurons in the SC.